Pengujian Kemampuan Daya Samak Cube Black dan Limbah Cair Gambir Terhadap Mutu Kulit Tersamak - Yeni, Gustri; Syafruddin, Dindin; Kasim, Anwar (Institution for Industrial Research and Standardization of Industry - Padang, 2016)
Leather tanning industries generally use sintetic tanner such as chrome (Cr+3) which can damage environment. Therefore, it is needed to find environmentally friendly tannery material, one is by using gambier. The aim of this research was to know tannic ability of gambier on goatâs leather and tuna fish. The gambier for tannery material contained high tannin (>70%) namely Cube black and liquid waste from gambier processing. Concentration of tannery material that would be used for tanned was 1 kg. Tanned leather was tested to tannery degree (DP) and physical test included pull strength, elongation, and rip strength, at same treatment compared to chrome tannery. Test results leather tanned showed that, the higher the concentration of tannery material the higher the results of DP, and the physical characteristic was better. Tanned leather from goat that used Cube black gambier concentration at 4% gave DP value approximately equal to chrome tanner (38,45% and 36,60%). For tanned tuna fish gave value of DP were 39,57% and 31,35%. Tannery material of gambier gave value of pull strength, rip strength, and elongation were higher than chromeâs. The value of pull strength of goatâs leather was 730,37 kg cm-2, tuna fish was 353,33 kg cm-2 got from liquid waste tanner. The value of rip strength fof goatâs leather was 353,33 kg cm-2, tuna fish skin 29,96 kg cm-2, and elongation value from tuna fish skin 202,0% was gotten from Cube black gambier. The result of the research showed that tannery material of gambier had tannery characteristic that can replace tanner of chrome.ABSTRAKIndustri penyamakan kulit umumnya menggunakan bahan penyamak sintetis seperti krom (Cr+3) yang dapat merusak lingkungan. Untuk itu, perlu dicari bahan penyamak yang ramah lingkungan, diantaranya menggunakan gambir. Tujuan penelitian ini adalah mengetahui daya samak gambir terhadap kulit kambing dan ikan tuna. Gambir untukÂ bahan penyamak mengandung kadar tanin tinggi (>70%) adalah Cube black dan limbah cair pengolahan gambir. Konsentrasi bahan penyamak yang digunakan dalam perlakuan adalah 2%, 3% dan 4% dengan berat kulit yang akan disamak sebanyak 1 kg. Kulit tersamak diuji terhadap derajat penyamakan (DP) dan uji fisik meliputi kekuatan tarik, kemuluran dan kekuatan sobek. Pada perlakuan yang sama dibandingkan dengan penyamak krom. Hasil uji kulit tersamak menunjukkan makin tinggi konsentrasi bahan penyamak makin tinggi nilai DP dan sifat fisik kulit makin baik. Kulit tersamak dari kambing menggunakan Cube black gambir pada konsentrasi 4% menghasilkan nilai DP mendekati sama dengan penyamak krom (38,45% dan 36,60%). Untuk kulit ikan tuna tersamak menghasilkan nilai DP 39,57% dan 31,35%. Bahan penyamak gambir menghasilkan nilai kekuatan tarik, kekuatan sobek dan kemuluran lebih tinggi dari penyamak krom. Nilai kekuatan tarik kulit kambing 730,37 kg/cm2, ikan tuna 353,33 kg/cm2 diperoleh dari penyamak limbah cair. Nilai kekuatan sobek kulit kambing adalah 353,33 kg/cm2, kulit ikan tuna 29,96 kg/ cm2 dan nilai kemuluran kulit ikan tuna 202,0% diperoleh dari Cube black gambir. Hasil penelitian menunjukkan bahan penyamak gambir memiliki sifat penyamak yang dapat menggantikan penyamak krom.